Examining the influence of advocacy advertising credibility on consumer's perception or commercial corporate image - Chong, Yee Lee (2000)
Dramatic changes in the environment, ranging from developments of public concern on physical, social and economic issue to the emergence of a global marketplace - representing both threat and opportunity - is increasingly competitive nature of business market. Hence, commercial firms are beginning to establish, alter or maintain the corporation's identity and one of the way most rapidly used is advocacy ad. This study stress the importance of understanding on how consumers make sense of the advocacy advertising and contribute to corporate image generally perceived. Preliminary, exploratory research was conducted to gain ideas on how did interviewees link advocacy ad credibility and advertiser image. In the proceeding stage, questionnaires with a sample advocacy ad were distributed targeting participants with variety of ages, education and economic background to gain deeper insight of their perception of the advocated issue and advertiser image. The present research proposed that consumers' main concern in evaluating a sponsor image is the ad attractiveness, followed by trustworthiness and advocacy message value congruency. However, consumers are less concern of advertiser expertise and action beyond words of its advocated position. In addition, consumers were found to be passively involved with the advocated issue. It would be interesting to enhance more topical coverage in future research to test the validity of the findings, e.g. exploration on expanding or modifying present measurable dimensions of organizational credibility, testing the effect of commercial and non-commercial advocacy speech in detail, creativity of advocacy advertising, effectiveness of fear or threat appeals compared to constructive messages, and impact of consumer involvement and confidence in the product as mediating variables.